Beauty and the Body of the Beholder: Raters' BMI Has Only Limited Association with Ratings of Attractiveness of the Opposite Sex. Issue 3 (21st February 2018) - Wang, Guanlin; Ekeleme‐Egedigwe, Chima A.; El Hamdouchi, Asmaa; Sauciuvenaite, Justina; Bissland, Ruth; Djafarian, Kurosh; Ojiambo, Robert; Ramuth, Harris; Holasek, Sandra; Lackner, Sonja; Diouf, Adama; Hambly, Catherine; et al.
Abstract : Objective: Assortative mating for adiposity increases the genetic burden on offspring, but its causes remain unclear. One hypothesis is that people who have high adiposity find other people with obesity more physically attractive than lean people. Methods: The attractiveness of sets of images of males and females who varied in adiposity were rated by opposite sex subjects (559 males and 340 females) across 12 countries. Results: There was tremendous individual variability in attractiveness ratings. For female attractiveness, most males favored the leanest subjects, but others favored intermediate fatness, some were indifferent to body composition, and others rated the subjects with obesity as most attractive. For male images rated by females, the patterns were more complex. Most females favored subjects with low levels of adiposity (but not the lowest level), whereas others were indifferent to body fatness or rated the images depicting individuals with obesity as the most attractive. These patterns were unrelated to rater BMI. Among Caucasian males who rated the images of the thinnest females as being more attractive, the magnitude of the effect depended on rater BMI, indicating limited "mutual attraction." Conclusions: Individual variations in ratings of physical attractiveness were broadly unrelated to rater BMI and suggest that mutual attraction is an unlikely explanation for assortative mating for obesity.